IMPLEMENTASI PENDIDIKAN KARAKTER MELALUI KEGIATAN PEMBINAAN PESERTA DIDIK DALAM MEMBENTUK WATAK KUAT-POSITIF - Firman Mansir; Muhammad Abrar Parinduri; Sofyan Abas (Universitas Sarjanawiyata Tamansiswa, 2020)
This study examined character education in a different paradigm. In this case, character education was implemented through a variety of activities that existed in educational institutions, especially student coaching activities. Not all students’ activities were able to instill the values of character education, so it was expected that through student coaching activities, character education could be achieved as it was formulated in the government regulations. The purpose of character education was to create students with good personalities. Once they grew up with an excellent character, the students would grow with their capacity and commitment to do the best things and do everything right and tended to have goals in life. Effective character education was found in a school environment that allowed all learners to show their potency to achieve significant goals. By doing so, character education in various student development activities could be connected and provided positive energy for the development of students in educational institutions. This research was a library study (library research) that utilizedliterary materials as the primary source and employed a qualitative approach. Therefore, the researcher exploredseveral data both primary and secondary data with concrete steps as follows: read and examine in-depth primary data such as books which are the results of the priorstudies, theses and dissertations related to character education and government regulations particularly the Regulation of the Minister of National Education of the Republic of Indonesia Number 39 of 2008. Therefore, the implementation of character education in the activities of fostering learners became very important to revive the values of character to students that were still doubtful at this time. Thus, the Regulation of the Minister of National Education could be executedby what has been aspired so far.